Risk Perception, Unhealthy Behavior, and Anxiety Due to Viral Epidemic Among Healthcare Workers: The Relationships With Depressive and Insomnia Symptoms During COVID-19 - Lee, Jukab; Lee, Hyuk Joo; Hong, Youjin; Shin, Yong-Wook; Chung, Seockhoon; Park, Jangho (Frontiers in Psychiatry, 2021)
We aimed to investigate the relationship between mental health problems and unhealthy behaviors among healthcare workers in response to the COVID-19 pandemic. Using an online survey, we collected data on healthcare workers’ perception regarding COVID-19 exposure in a work unit. Workers’, depression, insomnia, and anxiety symptoms were assessed using the Patient Health Questionnaire-9, Insomnia Severity Index, and Generalized Anxiety Disorder-7 scale, respectively. Work-related stress and anxiety in response to the viral epidemic were measured using the Stress and Anxiety to Viral Epidemic-9 (SAVE-9) scale. We found that, work-related stress and anxiety in response to the viral epidemic was associated with female sex, perception of the workplace as being dangerous, and depressive symptoms. Unhealthy behaviors, such as smoking and drinking as coping behaviors during the pandemic, were associated with male sex, young age, depression, and insomnia. During the COVID-19 pandemic, it is necessary to closely observe the patterns of work-related stress and anxiety reactions among healthcare workers to reduce their burnout.